U.S. Chinese relations in a Global Perspective - Fawcett, Alicia (2014)
Title: Diplomacy with Chinese Characteristics: The Cultural Aspect of Chinese Foreign Policy in the Example of Sino-American Relations Ambiguity in answers, lack of communication or justification of actions have resulted in a negative depiction of Sino-American relations. I would like to prove the cultural significance as a major factor in influencing Chinese foreign policy regarding the example of Sino-American relations. By applying elements of constructivism, one is able to understand the cultural perspective of Chinese foreign policy in the example of Sino-American relations. Furthermore, this is proven through philosophical application of game theory stratagem.